Coping with Risk through Mismatches : Domestic and International Financial Contracts for Emerging Economies - de la Torre, Augusto; Schmukler, Sergio L. (World Bank, Washington, D.C., 2013)
The authors argue that short termism, dollarization, and the use of foreign jurisdictions are endogenous ways of coping with systemic risks prevalent in emerging markets. They represent a symptom at least as much as a problem. These coping mechanisms are jointly determined and the choice of one of them involves risk tradeoffs. Various conclusions can be derived from the analysis. First, because of the dominance of dollar contracts over short-duration contracts, dedollarization might be much more difficult to achieve than often believed. Second, one-dimensional policies aimed at reducing currency and duration mismatches might just displace risk and not diminish it. Third, as systemic risks rise, the market equilibrium settles in favor of investor protection against price risk (through dollar and short-duration contracts) at the expense of exposure to credit risk. Finally, the option value to litigate in the event of default might explain this equilibrium outcome.